2021
DOI: 10.3390/land10020093
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Perception and Public Participation for the Conservation and Valorization of Cultural Landscapes: The Case of the Cinque Terre and Porto Venere UNESCO Site

Abstract: Europe retains a great variety of cultural landscapes that constitute a significant part of the European cultural heritage. In the last decades, these high-quality landscapes are facing several challenges due to socio-economic transformations that often compromise their integrity. This situation is even worse for terraced landscapes, as in the case of the Porto Venere and Cinque Terre UNESCO World Heritage List site. The Management Plan developed for this area needs to deal with different issues: abandonment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
2
19
0
6
Order By: Relevance
“…They are aware of issues that threaten terraces, but at the same time, they seem to be quite optimistic about their future enhancement. These results also agree with Santoro et al [60], who reported that farmers in Cinque Terre recognized terraced vineyards as the most important land use.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…They are aware of issues that threaten terraces, but at the same time, they seem to be quite optimistic about their future enhancement. These results also agree with Santoro et al [60], who reported that farmers in Cinque Terre recognized terraced vineyards as the most important land use.…”
Section: Discussionsupporting
confidence: 93%
“…Respondents were not identifiable by their answers and consented to the use of their anonymous answers. According to many authors who showed the efficacy of using images in questionnaires focusing on landscape perception, a series of images were presented to the respondents [60,61].…”
Section: Evaluation Of Winegrowers' Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, results of our survey are coherent with similar studies. Santoro et al [48] report for the UNESCO area (that is bigger than the 5TNP) an increase of woodlands and shrubland from 55% to 77% in the period 1973-2010. It is, in fact, recognized that, in the last decades, a significant reforestation trend is affecting European rural areas, mainly in Mediterranean countries [50][51][52], as a consequence of natural and human driven processes [53].…”
Section: Discussionmentioning
confidence: 98%
“…The local population, especially farmers, perceive the abandonment of terraced cultivations, and the consequent reforestation and hydrogeological risk, as the main factors threatening the identity of the place [48]. Regarding this, it is necessary to highlight that in the last years there has been a slow but perceptible return by some young people to agricultural activities, together with the spread of local associations of citizens who are involved in restoring dry-stone walls, removing shrubs from abandoned terraces and turning them back into cultivated areas.…”
Section: Discussionmentioning
confidence: 99%